Relationship between the global electric circuit and electrified cloud parameters at diurnal, seasonal, and interannual timescales. Issue 16 (23rd August 2017) - Lavigne, Thomas; Liu, Chuntao; Deierling, Wiebke; Mach, Douglas
Abstract: In the early 1900s, J. W. Whipple began to validate C. T. R. Wilson's global electric circuit (GEC) hypothesis by correlating the diurnal variation of global thunder days with the diurnal variation of the fair weather electric field measured by the Carnegie Cruise. This study applies 16+ years of precipitation feature (PF) data from the Tropical Rainfall Measuring Mission, including lightning data from the Lightning Imaging Sensor, alongside 12 years of electric field measurements from Vostok, Antarctica, to further examine this relationship. Joint diurnal‐seasonal variations of the electric field are introduced and compared with a variety of PF parameters that are potentially related to the GEC. All tested PF parameters showed significant correlations to the electric field on the joint seasonal‐diurnal timescale, with the flash rate and volume of 30 dBZ between the −5°C and −35°C isotherms showing the best linear correlations with R 2 values of 0.67 and 0.62, respectively. Furthermore, these relationships are analyzed during the two different phases of the El Niño–Southern Oscillation. Results show different seasonal‐diurnal variations of the electric field during El Niño and La Niña periods, with enhancements in the electric field between the months of January through April at 16–24 UTC in La Niña years. A similar trend is shown in global PF parameters, indicating relationships between the variations seen in the fair weather electric field and the variations of global PFs at diurnal, seasonal, and interannual timescales. This provides further evidence that PFs around the globe have a direct connection to the GEC. Key Points: Determines the TRMM electrified cloud parameters that have the best joint seasonal‐diurnal correlation to the global electric circuit Finds the differences in the measured GEC between the two ENSO phases. Distinct differences can be seen in the GEC between the two phases Determined that similar patterns of seasonal‐diurnal variation as the GEC can be seen in the TRMM parameters during the two phases of ENSO